The effects of disease lesions and amoxicillin treatment on the physiology of SCTLD-affected corals - Neely, Karen L.; Whitehead, Robert F.; Dobler, Michelle A. (Frontiers in Marine Science, 2024)
Metrics of coral physiology can be used to identify changes in coral health due to environmental stressors or management actions. One of the most unprecedented stressors to Caribbean corals is the spread of stony coral tissue loss disease (SCTLD), which also resulted in the novel management action of in-water amoxicillin treatments on active disease lesions. Though highly effective at halting lesions and preventing coral mortality, possible unintended consequences of topical application of amoxicillin to coral tissue were unknown. We used in-water instrumentation to measure and compare photosynthesis (P), respiration (R), P/R ratios, and calcification of corals that were visually healthy, actively diseased, and diseased but treated with amoxicillin paste. Measurements occurred across three time points and two species – Orbicella faveolata and Montastraea cavernosa. Across all metrics, treatment type did not cause significant differences, indicating that neither SCTLD lesions nor amoxicillin treatments impacted the physiology of adjacent tissues. There were significant variations among time points, which may have resulted from changes to coral health across the reef, variations due to environmental variables, or other unknown factors. We suggest that physiological metrics could be an interesting way to fate track coral health across short- and long-term timeframes. We also conclude that amoxicillin treatments as a tool to halt SCTLD are not detrimental to respiration, photosynthesis, or calcification rates of adult corals.